SEVICIA (PHYSICAL ABUSE) AND LEGAL LAWSUIT LIKE EXAMPLES OF DOMINATION AND RESISTANCE BETWEEN OWNERS AND BLACK SLAVES IN THE SANTIAGO, LATE COLONIAL PERIOD. THE CASE OF THE SLAVE THADEA ARANGUEZ, 1775-1776. - Duarte Sepúlveda, Natalia (Revista de Historia Social y de las Mentalidades, 2014)
The present article invites us to bring us over to  the topic to the study of the sevicia - use of the  excessive violence on the part of the owners - as  element of colonial domination, exercised on  the black slaves in the city of Santiago in the  second half of the 18th century. Together with  it, the reaction of the subjects dominated often  is far from a passive and submissive attitude.  These demonstrate a rejection to the domination  imposed by means of different ways, there being  constituted what is named a resistance. The slave, on having taken knowledge of  his juridical condition, uses the legal lawsuit  as a specific way of resistance opposite to  the domination. The juridical practice is a  resource that the secondary subjects use during  the colonial studied epoch, with the aim of  reclaim essential prerogatives and to face to the  estigmatización and prejudices with those who  were loading the above mentioned subjects in a  scene of deep social differentiations.
Keywords: Domination; Social Control; Resistance; Sevicia; Lawsuit; Otherness